Influence of Ligand Functionalization of UiO-66-Based Metal-Organic Frameworks When Used as Sorbents in Dispersive Solid-Phase Analytical Microextraction for Different Aqueous Organic Pollutants - Iván Taima-Mancera; Priscilla Rocío-Bautista; Jorge Pasán; Juan H. Ayala; Catalina Ruiz-Pérez; Ana M. Afonso; Ana B. Lago; Verónica Pino (Molecules, 2018)
Four metal-organic frameworks (MOFs), specifically UiO-66, UiO-66-NH2, UiO-66-NO2, and MIL-53(Al), were synthesized, characterized, and used as sorbents in a dispersive micro-solid phase extraction (D-µSPE) method for the determination of nine pollutants of different nature, including drugs, phenols, polycyclic aromatic hydrocarbons, and personal care products in environmental waters. The D-µSPE method, using these MOFs as sorbents and in combination with high-performance liquid chromatography (HPLC) and diode-array detection (DAD), was optimized. The optimization study pointed out to UiO-66-NO2 as the best MOF to use in the multi-component determination. Furthermore, the utilization of isoreticular MOFs based on UiO-66 with the same topology but different functional groups, and MIL-53(Al) to compare with, allowed us for the first time to evaluate the influence of such functionalization of the ligand with regards to the efficiency of the D-µSPE-HPLC-DAD method. Optimum conditions included: 20 mg of UiO-66-NO2 MOF in 20 mL of the aqueous sample, 3 min of agitation by vortex and 5 min of centrifugation, followed by the use of only 500 µL of acetonitrile as desorption solvent (once the MOF containing analytes was separated), 5 min of vortex and 5 min of centrifugation. The validation of the D-µSPE-HPLC-DAD method showed limits of detection down to 1.5 ng·L−1, average relative recoveries of 107% for a spiked level of 1.50 µg·L−1, and inter-day precision values with relative standard deviations lower than 14%, for the group of pollutants considered.